Shakespeare's sonnets reconsidered - Butler, Samuel, 1835-1902.
Includes unbound annotated copy of the sonnets of Shakespeare.
Author.
Collection material in English.
Keywords: Shakespeare, William, -- 1564-1616.; Literature; Authors